A comparative analysis of penitentiary management systems in Chile, Spain and the United Kingdom - Díaz-Villavicencio, G. (2017)
Objective: This research paper aims to establish a comparative study of penitentiary systems in Chile, Spain and the UK. It aims are threefold: i) to determine the socio-economic investment in prisons in the aforesaid countries; ii) to evaluate the socio-economic gaps that exist between Chile, Spain and the UK in the field of prison management; and iii) to evaluate what the most significant references or benchmarks are for prison management in the three countries mentioned in this study. The paper establishes Chile as the basis of this comparison (It is also the least developed country within this group- according to the OECD). The nine -year study period is set within the context of important changes within two of the key countries in this study. For Chile, the context is the penal process reform; for Spain, the context is the penal system itself. For the UK, however, it looks more at the legal and structural systems (which remained fairly constant during the nine-year period). Design/methodology/focus: The methodological design is descriptive. For this study, we reviewed secondary sources such as reports, online digital archives, academic papers, as well as prison studies. Conclusions: The results of this study indicate that Chile reduced its economic gap (in terms of inmate numbers) by 49%, that is, when comparing its figures with Spain. Conversely, the economic gap between Chile and the UK was calculated at 11%. The period of study for this paper comprises nine years, i.e. from 2000-2008. The study shows that there was an investment per capita of $2. 89 more per inmate compared with the figures for Spain. On the other hand, the figure for the UK was $36.41 higher than the figure for Chile. Notwithstanding, prison investment in Chile and Spain is still somewhat ineffective, especially when we evaluate the current situation in light of other more complex themes such as the management of inmates' reinsertion into society. Our findings conclude that the UK serves as an important benchmark/case study to be emulated in other countries, especially for the long-term management of prisons. Our study likewise suggests that Chile should maintain a healthy and stable economic gap within this field, that is, when we compare its figures with Spain. On the other hand, Chile requires a more moderate socio-economic gap in prison management when we compare its prison figures with those of the UK. For this reason, it is important to establish a new course of action which incorporates better leadership in the knowledge management of penitentiary institutions, and where there is a greater social emphasis. Limitations - implications of the research: The penitentiary benefits examined in the three countries in this study are not immediately visible seeing that the social reinsertion mechanisms are seen as being somewhat superfluous, and/or ineffective in the long-run. The latter is due to certain practices in penal laws that are being used today in a number of case studies, and also because of the time frames of when the new penal reforms and regulations are being implemented. Furthermore, there is a lack of data concerning variables such as the quality of investment and the rate of investment (%), both of which tend to limit the scope of our research. Practical implications of the study: As there are some issues that have not been dealt with in this study in detail, it would be necessary to carry out further comparative studies - for example measuring penitentiary efficiency in Chile over varying time frames and under different socio-economic conditions. After conducting an analysis of some key variables, however, it was considered pertinent to replicate some of these variables in other countries such as Brazil, where there exists a similar penitentiary system to the one(s) described in this study. Furthermore, after considering additional variables such as earnings and unemployment figures, and after witnessing the expansion of these types of studies in other regions in Latin America, it was deemed pertinent to enhance both the measurement of prison management statistics and the quality of prison/inmate management. Originality/value: This research paper provides information and data that were not previously known about the penitentiary system in three selected countries. What is more, it serves as a useful comparative study of prison statistics in Chile, Spain, and the UK. Finally, it establishes an important point benchmark (the UK case study), which could be successfully emulated by other countries as a socio-economic investment model.